Wicca, Esotericism and Living Nature: Assessing Wicca as Nature Religion - Pearson, Jo (Pomegranate, 2000)
'Nature Religion' is a relatively recent academic construct under which a variety of religions have been grouped including Paganism, eco-spirituality, and indigenous religions.